A competency-based approach: training specialists with higher education in Kazakhstan - Ismukhanova, G. G.; Sansyzbayeva, A. R. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2016)
This article provides a theoretical analysis of the scientific literature on the issue of competence, on the basis of which are provided definitions and applications of the terms competency, competence, competitive, qualification, experience, ability, and skill, including the concept of hard skills and soft skills. The theoretical foundation of the article is based on the scientific developments of international, Russian, and Kazakhstani scientists who have studied workforce preparation and the transitioning from a «qualification-based» approach to a «competency-based» model of education. The issue is a timely one, due to the need to produce competitive and competent specialists in the context of current forms in Kazakhstan’s higher education system. The primary benefit of adopting a competency-based model is meeting the needs of the labor market while providing jobs for new graduates. This article describes key opportunities, recommendations, and principles for the development of professional competence, including criteria and indicators for professional competency develop-ment among students, the personalization of education, and the development of cre-ative abilities. The primary objective of this article is to provide a theoretical basis for the grad-ual adoption of a competency-based model in the Kazakhstan’s higher education system. The development of a competency-based model in the national context will contribute to the success of further modernization of the higher education system as the central link to the national economy. At this stage, the authors have focused on competencies and competent undergraduates, graduates, and PhD students. The ar-ticle includes significant discussion of the opportunity to establish evaluation criteria for the professional competence of students based on the competence ladder, which broadens the function of the educational system as a three-sided process, with par-ties connected through both vertical and horizontal relationships. The future marker of students’ professional competence will be their ability to create new knowledge, characterized as creative conscious competence, expanding on the traditional five levels of competence which limit the process of acquiring competencies to learning from a teacher and mentor. Returning science to the university will contribute to the integration of specialists into international projects. This will in turn allow them to independently develop their own areas of study and schools, capable of collaborat-ing with international partners and universities. The conclusion considers key approaches for adopting and piloting a compe-tency-based model in the system of higher education in Kazakhstan.